2020
DOI: 10.1515/pac-2019-0502
|View full text |Cite
|
Sign up to set email alerts
|

Global occurrence, chemical properties, and ecological impacts of e-wastes (IUPAC Technical Report)

Abstract: The waste stream of obsolete electronic equipment grows exponentially, creating a worldwide pollution and resource problem. Electrical and electronic waste (e-waste) comprises a heterogeneous mix of glass, plastics (including flame retardants and other additives), metals (including rare Earth elements), and metalloids. The e-waste issue is complex and multi-faceted. In examining the different aspects of e-waste, informal recycling in developing countries has been identified as a primary concern, due to widespr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 179 publications
0
27
0
Order By: Relevance
“…Waste is one of the main anthropogenic sources of HM in the environment 26 , 30 , with electrical and electronic waste (e-waste) alone containing 56 metals 31 . We focus here on 8 HM ubiquitous in wastes of different kinds.…”
Section: Discussionmentioning
confidence: 99%
“…Waste is one of the main anthropogenic sources of HM in the environment 26 , 30 , with electrical and electronic waste (e-waste) alone containing 56 metals 31 . We focus here on 8 HM ubiquitous in wastes of different kinds.…”
Section: Discussionmentioning
confidence: 99%
“…The consequence of non-existent or inadequate infrastructure to manage the disposal and recycling of the large percentage of the e-wastes effectively is habitual contamination of the environments and a significant exposure of people, including children, to harmful chemicals ( Lundgren, 2012 ; Olafisoye et al., 2013 ; Heacock et al., 2016 ; Singh et al., 2020 ). The contaminants, which might occur directly through the recycling process or indirectly by ecological exposure, pose considerable risks to human health ( Purchase et al., 2020 ; Alabi et al., 2021 ; Kumar and Gupta, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that per capita generation of e-waste is the highest in Norway (~ 28.5 kg). US and Canada produce 20 kg of e-waste (per capita) whereas countries in Latin America contribute 10% of generated ewaste worldwide (Purchase et al 2020). In Asia, China is the highest e-waste generator (total) whereas the US is the annual highest global e-waste producer (10 MT, 2017) (Dwivedy and Mittal 2010;Wath et al 2010; Wath et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the generation of e-waste was 42 MT in 2014 occupying about 5% of the total generated municipal solid waste and, by 2017 increased up to 72 MT (Ongondo et al 2011; Ikhlayel 2016). The growth of e-waste has been exponentially expanding especially over the last two decades (Dasgupta et al 2014;Purchase et al 2020). The e-waste generation growth rate (both globally and regionally) clearly indicates that the existing management protocol of e-waste is complex and multifaceted that needs serious policy attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation